Rancang Bangun Aplikasi Pemberitahuan Jadwal Praktikum Berbasis SMS Gateway Menggunakan PHP dan MySQL (Studi Kasus Laboratorium Fakultas Ilmu Komputer Universitas Kuningan) - abbas, cecep juliansyah (BUFFER INFORMATIKA, 2016)
ABSTRACTÂ Kuningan University (UNIKU) is one of the education institutions in Kuningan. UNIKU has 5 faculties and one of them is Faculty of Computer Sciences (FKOM). Students of FKOM not only studied the subject of computer science theoritically but also lab work subjects. In the process of submitting a schedule of lab work course in faculty of computer science is still in a conventional way by printing schedule and posting schedule on information boards, this way is still less effective because it can not be known by students who are not in campus. By applying the SMS Gateway technology, the schedule and information at the Faculty of Computer Sciences Kuningan University can be disseminated through SMS (Short Message Service). Implementation of the SMS gateway schedules provides ease of access to the lab work schedule. The application will send the schedule SMS to students and students can also request the schedule recorded on the application by sending SMS format request information schedule. The programming language for creating scheduling notification apps is using PHP programming language, for databases using MySQL, using Apache as a web server, and Gammu as the SMS service